2020
DOI: 10.1073/pnas.2003352117
|View full text |Cite
|
Sign up to set email alerts
|

Complementary regulation of caspase-1 and IL-1β reveals additional mechanisms of dampened inflammation in bats

Abstract: Bats have emerged as unique mammalian vectors harboring a diverse range of highly lethal zoonotic viruses with minimal clinical disease. Despite having sustained complete genomic loss of AIM2, regulation of the downstream inflammasome response in bats is unknown. AIM2 sensing of cytoplasmic DNA triggers ASC aggregation and recruits caspase-1, the central inflammasome effector enzyme, triggering cleavage of cytokines such as IL-1β and inducing GSDMD-mediated pyroptotic cell death. Restoration of AIM2 in bat cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 80 publications
1
61
0
Order By: Relevance
“…One of the key findings that has previously been highlighted is the dampened activation of the inflammasome complex in bats. Previous studies have demonstrated altered inflammasome activation in bats, including the loss of the PYHIN gene family 127 , dampened NLRP3 72 and reduced function of caspase-1 and/or IL-1β 131 (Fig. 3).…”
Section: Learning From Batsmentioning
confidence: 84%
See 1 more Smart Citation
“…One of the key findings that has previously been highlighted is the dampened activation of the inflammasome complex in bats. Previous studies have demonstrated altered inflammasome activation in bats, including the loss of the PYHIN gene family 127 , dampened NLRP3 72 and reduced function of caspase-1 and/or IL-1β 131 (Fig. 3).…”
Section: Learning From Batsmentioning
confidence: 84%
“…Both NLRP3 and AIM2 converge on their downstream effector caspase-1, which is responsible for cleavage of the inflammatory cytokines IL-1β and IL-18, and simultaneously unleashes inflammatory cell death (pyroptosis) through GSDMD 129,130 . Recent data reveal additional mechanisms of dampening at the level of downstream caspase-1 and IL-1β 131 , demonstrating a unique targeting of the inflammasome pathway for inhibition in bats. The high metabolic demands of flight could-in theory-lead to the release of metabolic by-products, including reactive oxygen species, ATP, damaged DNA and other danger signals that are known to trigger inflammasome activation.…”
Section: Mechanisms Of Immune Tolerancementioning
confidence: 99%
“…108 However, expression of ASC, CASP1, and IL-1β appeared to be not affected in bat immune cells like human cells. 108,109 Because of NLRP3 priming and altered LRR domain defects, bat immune cells show lesser formation ASC speck assemblies and reduced release of IL-1β cytokine. 108 Besides, bat cells show impaired pyroptosis and LDH release compared with human cells.…”
Section: Bat Coronaviruses Inflammasome Regulation and Immune Tolerancementioning
confidence: 99%
“…These include stimuli by inflammasome-derived cytokines produced by myeloid cells, including IL-1b and IL-18 (Tang et al, 2013;Ussher et al, 2014). In Pa, there is a dampened inflammasome signaling and subsequent inflammasome-derived cytokine production by myeloid cells following stimulations with lipopolysaccharide (Ahn et al, 2019;Goh et al, 2020), a major cell wall component of E. coli. Thus, it is tempting to speculate that the subdued inflammasome response by Pa myeloid APC may account for the lack of immediate effector responses by resting Pa MR1T cells.…”
Section: Access Isciencementioning
confidence: 99%
“…Data from a broad comparative genomic study indicate that bats are the only mammals to have lost the entire pyrin and HIN domain gene family, which codes for DNA sensors important for dsDNA-triggered inflammation . There are also lower levels of apoptosis-associated speck-like protein containing a CARD, caspase-1, as well as interleukin (IL)-1b secretion in bat immune cells following infection by various zoonotic viruses (Ahn et al, 2019;Goh et al, 2020). In addition, nucleotide-binding domain leucine-rich repeat and pyrin domain containing receptor 3 (NLRP3) activity appear to be reduced in the bat immune cells compared to human and murine counterparts (Ahn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%